Human Rights at the Court: Criticism of the Human Rights Courts in Indonesia - Yuwanda Tri Maryoga (Universitas Negeri Semarang, 2018)
As a court the Human Rights Court It was said in the preface of this book that efforts to protect human rights have been debated since the time when the 1945 Constitution was drafted at the BPUPKI, according to Hatta-Muh. Yamin, so that the state does not become a sovereign state, human rights need to be included in the Constitution, while Soekarno-Soepomo wanted the state to be founded with an understanding of kinship, while human rights were the result of individualism so that human rights were not included in the Constitution. The human rights contained in the 1945 Constitution also preceded human rights as contained in the Universal Declaration of Human Rights because this declaration was only established on December 10, 1948, enacted at the PPB general assembly in Paris.